Detection of Anisakidae larvae parasitizing Plagioscion squamosissimus and Pellona castelnaeana in the State of Pará, Brazil (Acta Scientiarum. Biological Sciences, 2017)
Five specimens of Plagioscion squamosissimus from Xingu River and ten specimens of Pellona castelnaeana from Mosqueiro Island, both in the State of Pará, Brazil, were examined to investigate the presence of anisakid nematodes, due to their zoonotic potential. Their parasitism indices and sites of infection were also determined. This is the first record of Anisakidae parasitizing Pellona castelnaeana. Four-hundred and eighty-four third-stage larvae (L3) of Anisakidae were found, of which 42 were found in P. squamosissimus and 442 in P. castelnaeana. The parasitism indices of the anisakid collected from the P. squamosissimus comprised prevalence (P) of 100%, mean infection intensity (MI) of 8.4, range of infection (RI) of 1-13, mean abundance (MA) of 8.4, and infection site (IS) in the abdominal cavity. P. castelnaeana showed P = 100%, MI = 44.2, RI = 10-114, MA = 44.2, and IS = abdominal cavity, cecum and stomach. The life cycle of these nematodes can be completed in the Amazon basin, since the two hosts fish are part of the cetacean diet of the region, which participate as final hosts. These findings have an important consequence on epidemiology of anisakiasis, so attention should be extended to human protection against this public health risk.